2014
DOI: 10.1136/bcr-2013-203174
|View full text |Cite
|
Sign up to set email alerts
|

Management of digital vasculopathy in systemic sclerosis: benefits of multiple courses of endothelin-1 receptor antagonists

Abstract: Two patients with scleroderma and recurrent digital ulcers (DUs) were treated with bosentan for 6 months. Treatment was associated with a reduction in the number of new DUs; however, DUs recurred on treatment discontinuation. This case report illustrates the positive response of digital vasculopathy to bosentan and describes the benefits of multiple bosentan treatment courses in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…515 Scleroderma patients develop autoantibodies directed against the ET A receptor, and antibody titers predict the occurrence of new ischemic digital ulcers, 516 as well as mortality in scleroderma patients with PAH. 517 Korn et al 518 first reported beneficial effects of ERA treatment on development of new ulcers, and observation confirmed by the RAPIDS-1 and RAPIDS-2 (Randomized, Double-Blind, Placebo-Controlled Study With Bosentan on Healing and Prevention of Ischemic Digital Ulcers in Patients With Systemic Sclerosis) found a 30% to 48% reduction in the numbers of new digital ulcers in scleroderma patients after therapy with bosentan (Table S1 in the online-only Data Supplement) 519,520 ; however, treatment did not affect progression and severity of existing digital ulcers 519 (Figure 4). In 2007, bosentan (Tracleer) received regulatory approval by the European Medicines Agency for scleroderma-related digital ulcers.…”
Section: Autoimmune Diseasesmentioning
confidence: 91%
See 1 more Smart Citation
“…515 Scleroderma patients develop autoantibodies directed against the ET A receptor, and antibody titers predict the occurrence of new ischemic digital ulcers, 516 as well as mortality in scleroderma patients with PAH. 517 Korn et al 518 first reported beneficial effects of ERA treatment on development of new ulcers, and observation confirmed by the RAPIDS-1 and RAPIDS-2 (Randomized, Double-Blind, Placebo-Controlled Study With Bosentan on Healing and Prevention of Ischemic Digital Ulcers in Patients With Systemic Sclerosis) found a 30% to 48% reduction in the numbers of new digital ulcers in scleroderma patients after therapy with bosentan (Table S1 in the online-only Data Supplement) 519,520 ; however, treatment did not affect progression and severity of existing digital ulcers 519 (Figure 4). In 2007, bosentan (Tracleer) received regulatory approval by the European Medicines Agency for scleroderma-related digital ulcers.…”
Section: Autoimmune Diseasesmentioning
confidence: 91%
“…In 2007, bosentan (Tracleer) received regulatory approval by the European Medicines Agency for scleroderma-related digital ulcers. 519 In the DUAL-1 and DUAL-2 (Macitentan for the Treatment of Digital Ulcers in Systemic Sclerosis Patients) randomized trials, macitentan (Opsumit ® ), 521 which unlike bosentan is ET A -selective, 80 did not reduce new digital ulcers in scleroderma patients. 521…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…The cases presented here have small- to medium-sized palmar arch-level vessel problems that seem continuous with CTD 9 . When ischemic ulceration or pain persists despite conservative and medical treatment, surgical treatment must be considered 10 . Surgical therapy consists of sympathectomy, reconstruction using a bypass graft and venous arterialization 6 .…”
Section: Discussionmentioning
confidence: 99%
“…9 When ischemic ulceration or pain persists despite conservative and medical treatment, surgical treatment must be considered. 10 Surgical therapy consists of sympathectomy, reconstruction using a bypass graft and venous arterialization. 6 Surgical sympathectomy strips the adventitia from the involved arteries to decrease pathologic sympathetic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Vasoconstriction following Raynaud phenomenon and structural change in blood vessels including intimal proliferation and obstruction leads to distal extremities specifically digital infarction and ulcer [2]. About 30 to 60% of scleroderma patients developed digital ulcers (DUs) in the course of their disease; these ulcers can affect the quality of life of the patients through the pain experienced and the delay in the healing process [3,4]. Notwithstanding, few studies have investigated the effective treatment processes, specifically for SSc DUs.…”
Section: Introductionmentioning
confidence: 99%